Molecular identification of cathepsin L gene from Chrysomya megacephala and Lucilia cuprina - Kayan, Imba (2014)
Chrysomya megacephala and Lucilia cuprina are among the most common blow flies in Malaysia. These blow flies are easily captured and can be found anywhere in Malaysia. The objective of this study was to investigate the presence of cathepsin L gene from C. megacephala and L. cuprina. The cathepsin L has a potential to become a good candidates for insect pest control. A total of 97 C. megacephala and 45 L. cuprina were captured from Sri Serdang wet market, Putra Food Court and Pasar Borong Selangor. These flies were divided into groups based on their morphological characteristics and reared in the insectary. For the more accurate identification of species, mitochondrial cytochrome c oxidase subunit 1 (CO1) gene of C. megacephala and L. cuprina was amplified and sequenced. Analyses by neighbour-joining methods showed the potential of this region to provide the necessary species-level identifications. A cDNA encoding a cathepsin L-like cysteine protease was isolated from C. megacephala and L. cuprina purified RNA by a PCR approach. Plasmid PCR products of the expected size (~500 bp) were visualized by agarose gel electrophoresis. Phylogenetic tree analysis demonstrated that the cathepsin L gene presence in C. megacephala and L. cuprina. This is the first report of cathepsin L gene from C. megacephala and L. cuprina in the world.